Bioactivity Test of Bitter Melon (Momordica charantia L.) Ethanol Extract As Larvacide on Aedes sp and Culex sp. - Reza Anindita; Elfira Mayasari; Ariani Diah Prastiwi; Rido Aji Alamsyah; Maulin Inggraini (Indonesian Journal of Biology Education, 2022)
Aedes aegypti and Culex sp. is a vector of dengue, filariasis, and malaria in Indonesia. One of the alternative efforts to control the spread of mosquitoes that are safe and harmless to the environment and humans can be done by giving natural ingredients that have the potential as larvicides, namely bitter melon. The purpose of this study was to determine the effect and effectiveness of bitter melon as a natural larvicide for Aedes aegypti and Culex sp. The design of this study was experimental using samples of bitter melon and fourth instar larvae of Aedes aegypti and Culex sp. The treatments in this study included ethanol extract of bitter melon with concentrations of 250 ppm, 500 ppm, 750 ppm and 1000 ppm, abate 1% as a positive control and aquades as a negative control. All treatments were given to the fourth instar larvae of Aedes aegypti Culex sp. each containing 20 larvae. Data analysis in this study was carried out by One-Way ANNOVA test, Independent sample t-test, and probit analysis. The results showed that the lowest-highest percentage of Aedes aegypti larvae mortality ranged from 26% - 85%, while Culex sp. ranged from 17% - 65%. The results of the ANOVA test showed significant differences between the treatment groups (P<0.05) in both Aedes aegypti and Culex sp. but the results of the Independent sample t-test showed no significant difference (P>0.05) between the Aedes aegypti and Culex sp. The results of the probit analysis showed that the LC50 value for Aedes aegypti was 728,789 ppm while Culex sp was 732,272 ppm. The conclusion of this study was that the administration of ethanol extract of bitter melon was more effective on the fourth instar larvae of Aedes aegypti than Culex sp.